Mass structure deformation monitoring using low cost differential global positioning system device - Azar, Ramin S.; Mohd Shafri, Helmi Zulhaidi (Science Publications, 2009)
In this study, a technique for monitoring bridge deformation with the simplest GPS device available was demonstrated. The accuracy of these observations was evaluated and the best approach for this purpose was suggested. The device used was the low cost GS20 Leica single frequency GPS, which is a basic GPS receiver for this study. This study was done during March, April and May 2008. Five points were selected along Putrajaya Seri Wawasan cable bridge, two on ends and three along the slope and one point as base station established outside bridge area on stable ground. Three observations epochs per point were conducted to assess the bridges stability. Virtual Rinex data were used for correcting base station observation. Results have shown that for limited usage and academic studies, these devices should be adequate. Switching to more precise requirements will need more investment on equipment.